2020
DOI: 10.1038/s41598-020-58866-y
|View full text |Cite
|
Sign up to set email alerts
|

Waste foundry sand/MgFe-layered double hydroxides composite material for efficient removal of Congo red dye from aqueous solution

Abstract: We aimed to obtain magnesium/iron (Mg/fe)-layered double hydroxides (LDHs) nanoparticlesimmobilized on waste foundry sand-a byproduct of the metal casting industry. XRD and ft-iR tests were applied to characterize the prepared sorbent. The results revealed that a new peak reflected LDHs nanoparticles. In addition, SEM-EDS mapping confirmed that the coating process was appropriate. Sorption tests for the interaction of this sorbent with an aqueous solution contaminated with congo red dye revealed the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 60 publications
(26 reference statements)
1
67
0
1
Order By: Relevance
“…As an alternative method, adsorption process in the treatment of dye-contaminated wastewaters can be used due to its simplicity, high efficiency, low costs, ease and flexibility of operation, easy desorption. In recent years, lots of novel adsorbents such as functionalized multiwalled carbon nanotubes [ 25 ], graphene oxide/clay nanocomposite [ 26 ], doped metal oxide [ 27 ] or derived from industrial solid wastes [ 28 ], agricultural solid wastes [ 29 , 30 ], biopolymers and their composites [ 31 , 32 , 33 ], sewage sludge [ 34 ], fly ash [ 35 ] have been reported in the literature. Although all the materials seem to be very promising, activated carbon is still the most common adsorbent for wastewaters treatment of in industrial plants contaminated with dyes.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative method, adsorption process in the treatment of dye-contaminated wastewaters can be used due to its simplicity, high efficiency, low costs, ease and flexibility of operation, easy desorption. In recent years, lots of novel adsorbents such as functionalized multiwalled carbon nanotubes [ 25 ], graphene oxide/clay nanocomposite [ 26 ], doped metal oxide [ 27 ] or derived from industrial solid wastes [ 28 ], agricultural solid wastes [ 29 , 30 ], biopolymers and their composites [ 31 , 32 , 33 ], sewage sludge [ 34 ], fly ash [ 35 ] have been reported in the literature. Although all the materials seem to be very promising, activated carbon is still the most common adsorbent for wastewaters treatment of in industrial plants contaminated with dyes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, activated carbon is widely used and commercially applied for dye decontamination, due to its impressive adsorption capacity 21 , but the high cost is a big limitation for its application 22 24 . The utilization of low-cost materials as suitable alternatives, such as biowastes 25 , chitosan based materials 26 , and natural inorganic materials 27 , 28 has gained attention recently. However, biomass waste materials are the preferred choice, owing to their abundance, low cost, biodegradability and efficiency 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, 2 M of NaOH and 0.2 M of Na 2 CO 3 were added to the solution and stirred for one hour to attain a pH of 7. This step was followed by drying the obtained solids at a temperature of 80 • C for 24 h [34]. The coated media was applied to remove cadmium (Cd 2+ ) ions from synthetic water.…”
Section: Preparation Of Coated Chicken Bonesmentioning
confidence: 99%
“…Figure 3 depicts the removal of Cd 2+ by both coated and uncoated chicken bone particles. It can be observed that two phases were involved in the metal sorption: the rapid sorption phase that involves passive surface reactions, such as chemical complexations (reaction between Cd 2+ ions and anion hydroxides forming the metal-ligand complex), or electrostatic sorption onto the surface of adsorbents [34,40]. In this rapid phase, a considerable rise in Cd 2+ removal was observed with the increase of contract time.…”
Section: Influence Of Contact Timementioning
confidence: 99%